Malaysia Mahathirism, hegemony and the new opposition - Hilley, John 1958- (Politics in contemporary Asia, 2001)
John Hilley provides a theoretically informed and insightful analysis of the Mahathir project. He examines how Prime Minister Mahathir Mohamed has translated the basis of the ruling bloc's legitimacy from coercive domination and ethnic card-playing into a consensual form of hegemonic support. Hilley looks at his strides in using developmentalist strategies, a language of post-ethnic nationalism, and the prospect of expanding social rewards.